Pigmentation of pattern formation in the butterfly wing of Papilio dardanus - Sekimura, T; Madzvamuse, A; Wathen, A; Maini, P (Unspecified, 2002)
We investigate pigmentation patterns in the butterfly wing of Papilio Dardanus by numerical simulations of a reaction-diffusion model on a geometrically accurate wing domain. Our results suggest that the wing coloration is due to a simple underlying stripe-like pattern of some pigment-inducing morphogen. In this paper, we present some of our numerical results and discuss the validity of our model by comparing our results with pictures of male and female wing patterns of the butterfly.